2017
DOI: 10.1155/2017/3083267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Preoperative Albumin and Globulin Ratio in Patients with Gastric Cancer Undergoing Treatment

Abstract: Background. The pretreatment albumin and globulin ratio (AGR) was an inflammation-associated factor which was related to the overall survival in various malignancies. The aim of this study was to evaluate the prognostic value of AGR in patients with gastric cancer. Method. This retrospective study included 862 cases pathologically diagnosed with gastric cancer. All patients were randomly divided into the testing group (431 cases) and validation group (431 cases). The relationships of AGR with clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 34 publications
2
34
1
Order By: Relevance
“…In addition to ALB and GLOB, the level of AGR was also analyzed. It has been reported that a low level of AGR has the potential to be a predictor for poor prognosis for breast cancer, gastric cancer, colorectal cancer, and lung cancer . However, in this study, the median of AGR was 1.5 (ranging from 0.6 to 2.3).…”
Section: Discussioncontrasting
confidence: 66%
“…In addition to ALB and GLOB, the level of AGR was also analyzed. It has been reported that a low level of AGR has the potential to be a predictor for poor prognosis for breast cancer, gastric cancer, colorectal cancer, and lung cancer . However, in this study, the median of AGR was 1.5 (ranging from 0.6 to 2.3).…”
Section: Discussioncontrasting
confidence: 66%
“…The prognosis of GC is also related to the tumor microenvironment and the interaction between the tumor and the host environment; hence, nonanatomical prognostic factors cannot be neglected. To date, numerous nonanatomical prognostic factors for predicting the prognosis of patients with GC have been evaluated, such as neutrophil‐lymphocyte ratio, Glasgow Prognostic Score, and albumin‐to‐globulin ratio …”
Section: Introductionmentioning
confidence: 99%
“…suggested that small-cell lung cancer patients with a pretreatment serum AGR <1.29 had a 1.35 times higher risk of death than those with an AGR ≥1.29. Mao et al 45. showed that a serum AGR <1.50 indicated poorer overall survival in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%